Basic psychological needs in Polish university level studies and their readiness for participation - Furtak, Przemysław (My University, 2012)
The following study, had three purposes. One was to examine, whether Basic Psychological Needs have an impact on the individuals participation level. Second step was to test the relation between Basic Psychological Needs and participation level depending on gender. Finally, the study was meant to examine self-discipline according to the KSAS questionnaire, in relation with the level of satisfaction of basic needs. Deci and Ryan’s Self- Determination Theory gave the theoretical background for this thesis. For the research, 106 participants from Polish universities completed two surveys. Basic Psychological Needs Scale BPNS by Deci and Ryan, and Self – Actualization Style Questionnaire KSAS by Zenon Uchnast. Regression analysis showed, that competence need, when fulfilled, have minor impact on the participation level. Study also proved, that there is a little moderation between genders. Women have more tendency to show their competence when it comes to participate in the university performance.

Następujące badanie, miało trzy cele. Jednym było zbadanie, czy podstawowe potrzeby psychologiczne mają wpływ na uczestnictwo. Drugim krokiem było stwierdzenie, czy istnieje stosunek między podstawowymi potrzebami psychologicznymi i poziomem uczestnictwa a pomiędzy płcią. Wreszcie, badanie miało możliwość sprawdzenia samodyscypliny według kwestionariusza KSAS, ze względu na poziom zaspokojenia podstawowych potrzeb. Proponowana przez Deciego i Ryana Teoria Samostanowienia jest tłem dla tej pracy. Do badania przystąpiło 106 uczestników z polskich uczelni, z których każdy wypełnił dwa kwestionariusze. Osoby badane uzupełniły Kwestionariusz Podstawowych Potrzeb Psychologicznych BPNS, autorstwa Deciego i Ryana oraz Kwestionariusz Stylów Samo aktualizacji Siebie KSAS Zenona Uchnasta. Analiza regresji wykazała, że potrzeba kompetencji, gdy spełniona, ma niewielki wpływ na poziom uczestnictwa. Badanie wykazało również, że istnieje pewna dysproporcja pomiędzy płciami. Kobiety mają większą tendencję, do pokazywania swojej kompetencji, jeśli chodzi o udział w aktywności uniwersyteckiej.
Podstawowe potrzeby psychologiczne w kontekście polskich studentów i ich gotowość do partycypacji
Keywords: psychologia; potrzeby psychologiczne; zaspokojenie potrzeb; studenci; partycypacja społeczna